Long-Term Clinical and Immunological Effects of Repeated Mesenchymal Stem Cell Injections in Patients With Progressive Forms of Multiple Sclerosis - Petrou, Panayiota; Kassis, Ibrahim; Ginzberg, Ariel; Halimi, Michel; Yaghmour, Nour; Abramsky, Oded; Karussis, Dimitrios (Frontiers in Neurology, 2021)
Background: Mesenchymal stromal stem cells(MSC) were shown to possess immunomodulatory and neurotrophic effects. In our previous trials we have shown that intrathecal(IT) and intravenous(IV) administration of MSC were safe and provided indications of beneficial clinical effects. Methods: An open prospective study with multiple injections of autologous MSC in 24 patients with active-progressive MS, who failed to respond to conventional immunomodulatory treatments. At inclusion, the mean age of the patients was 47.0±9.22 and the mean EDSS score 6.75±0.68(range:5.5-7.5). Patients were initially treated with 1 million MSC/kg of body weight (IT+IV) and subsequently with up to additional 8 courses of MSC, at intervals of 6-12 months. The duration of the trial was 4 years. Results: No serious, treatment-related adverse events were observed during the follow up period. 22 of the 24 patients were either stable or improved at the last follow-up visit. Ten patients had a lower than baseline EDSS at last follow up (9 were among those who received more than 2 treatments and one in the subgroup of 2 treatments or less, p=0.04). The mean EDSS score reduced from 6.75±0.68 at baseline to 6.42±0.84 at the last visit, during a median follow up period of 27.8 months (p=0.028). Immunological follow up showed a transient upregulation of regulatory T-cells and downregulation of the proliferative ability of lymphocytes. Conclusions: Repeated MSC treatments in patients with progressive-MS were shown safe at the short/intermediate term and induced clinical benefits (especially in patients treated with more than 2 injections) that lasted for up to 4 years, paralleled by short-term immunomodulatory effects.